Molecular Physics: Revealing Charge‐ and Temperature‐Dependent Movement Dynamics and Mechanism of Individual Molecular Machines (Small Methods 12/2019). Issue 12 (2nd December 2019) - Zhou, Ce; Li, Xingxing; Masai, Hiroshi; Liu, Zihao; Lin, Yuanwei; Tamaki, Takashi; Terao, Jun; Yang, Jinlong; Guo, Xuefeng
Abstract : In article number 1900464 by Jun Terao, Jinlong Yang, Xuefeng Guo, and co‐workers, charge‐ and temperature‐dependent movement dynamics and mechanism of molecular machines at the single‐event level are revealed by using stable graphene‐molecule‐graphene single–molecule junctions. These investigations conceptualize the capability of single‐molecule electronic devices to probe fast single–molecule physics, potentially revolutionizing the current technique to visualize single‐molecule chemical reactions or behaviors.